Bif-1 interacts with Beclin 1 through UVRAG and regulates autophagy and tumorigenesis - Takahashi, Yoshinori (2007)
Autophagy is an evolutionally conserved “self-eating” process. Although the genes essential for autophagy (termed Atg) have been identified in yeast, the molecular mechanism of how these Atg proteins control autophagosome formation in mammalian cells remains to be elucidated. Here, we demonstrate that Bif-1 (also known as Endophilin B1) interacts with Beclin 1 through UVRAG and acts as a positive mediator of the class III PI3-kinase (PI3KC3). In response to nutrition deprivation, Bif-1 localizes to autophagosomes where it colocalizes with Atg5, as well as LC3. Furthermore, loss of Bif-1 suppresses autophagosome formation. While the SH3 domain of Bif-1 is sufficient for binding to UVRAG, both the BAR and SH3 domains are required for Bif-1 to activate PI3KC3 and induce autophagosome formation. We also found that Bif-1 ablation prolongs cell survival under nutrient starvation. Moreover, knockout of Bif-1 significantly enhances the development of spontaneous tumors in mice. These findings suggest that Bif-1 joins the UVRAG-Beclin 1 complex as a potential activator of autophagy and tumor suppressor.